Modeling and Simulation of Turret Stabilization with Intelligent Algorithms - Ceceloglu, Ahmet Can; Yildirim, Tulay (ELSEVIER SCIENCE BV, 2019)
In this work, we study the problem of high precision turret control. Several control design strategies are applied to turret system to determine the applicability of each control design method and to characterize the achievable performance of turret system in precision control. A mathematical model of the turret is developed using state space equations. An intelligent controller has been developed for the stabilization of turret system with uncertain external disturbances. As an intelligent system is developed with Neural Network PID controller. MATLAB/Simulink and Neural network toolbox is used to set up application of turret system. (C) 2019 The Authors. Published by Elsevier Ltd.
Keywords: Turret; PID Control; Neural Network; Stabilization; Computer Science; Telecommunications